Risk Analysis Index and 30-Day Mortality after Brain Tumor Resection: A Multicenter Frailty Analysis of 31,776 Patients from 2012 to 2020 - Rumalla, Kavelin; Thommen, Rachel; Kazim, Syed Faraz; Segura, Aaron C.; Kassicieh, Alexander J.; Schmidt, Meic H.; Bowers, Christian A. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction The aim of this study was to evaluate the discriminative accuracy of the preoperative Risk Analysis Index (RAI) frailty score for prediction of mortality or transition to hospice within 30 days of brain tumor resection (BTR) in a large multicenter, international, prospective database.Methods Records of BTR patients were extracted from the American College of Surgeons National Surgical Quality Improvement Program (2012–2020) database. The relationship between the RAI frailty scale and the primary end point (mortality or discharge to hospice within 30 days of surgery) was assessed using linear-by-linear proportional trend tests, logistic regression, and receiver operating characteristic (ROC) curve analysis (area under the curve as C-statistic).Results Patients with BTR (N = 31,776) were stratified by RAI frailty tier: 16,800 robust (52.8%), 7,646 normal (24.1%), 6,593 frail (20.7%), and 737 severely frail (2.3%). The mortality/hospice rate was 2.5% (n = 803) and was positively associated with increasing RAI tier: robust (0.9%), normal (3.3%), frail (4.6%), and severely frail (14.2%) (p < 0.001). Isolated RAI was a robust discriminatory of primary end point in ROC curve analysis in the overall BTR cohort (C-statistic: 0.74; 95% confidence interval [CI]: 0.72–0.76) as well as the malignant (C-statistic: 0.74; 95% CI: 0. 67–0.80) and benign (C-statistic: 0.71; 95% CI: 0.70–0.73) tumor subsets (all p < 0.001). RAI score had statistically significantly better performance compared with the 5-factor modified frailty index and chronological age (both p < 0.0001).Conclusions RAI frailty score predicts 30-day mortality after BTR and may be translated to the bedside with a user-friendly calculator (https://nsgyfrailtyoutcomeslab.shinyapps.io/braintumormortalityRAIcalc/). The findings hope to augment the informed consent and surgical decision-making process in this patient population and provide an example for future study designs.
Keywords: frailty; Risk Analysis Index; brain Tumor; neuro-oncology; National Surgical Quality Improvement Program